2012
DOI: 10.4236/jct.2012.34035
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Efficacy of Nimotuzumab, an Anti-Egfr Monoclonal Antibody as a Single Agent Therapy in Human GBM u87mg Xenografts

Abstract: Background: The poor prognosis of patients with high-grade glioma multiform (GBM) has led investigators to the search of new therapeutic strategies. Current treatment includes surgery when possible, radiotherapy and chemotherapy. Molecular-targeted therapies are in the process of clinical testing, and promising agents include monoclonal antibodies. Our study examined the antitumor activity of three different single therapies in nude mice bearing both subcutaneous and orthotopic brain xenografts of the U87MG hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…According to a previous report, the treatment with TMZ caused a substantial growth delay of U87MG xenografts tumor, while irradiation did not affect tumor growth [33]. Here, we also confirmed that TMZ had higher anticancer effects than irradiation in U87MG xenografts.…”
Section: Resultssupporting
confidence: 89%
“…According to a previous report, the treatment with TMZ caused a substantial growth delay of U87MG xenografts tumor, while irradiation did not affect tumor growth [33]. Here, we also confirmed that TMZ had higher anticancer effects than irradiation in U87MG xenografts.…”
Section: Resultssupporting
confidence: 89%
“…Recent study corroborated that Nimotuzuma could effectively repress A431 cells proliferation, angiogenesis, and evoke apoptosis in squamous cell carcinoma (Gonzã¡Lez, Barquinero, Lee, Garcã­A, & Casacã³, ). Diaz et al () revealed that Nimotuzuma significantly restrained the proliferative activity of tumor cells, and also impeded tumor formation in glioblastomas. Based on these existing research works, we probed the influences of Nimotuzuma in OS cells proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect can be reversed by administering nimotuzumab which increases apoptosis by reducing the production of VEGF, leading to reduced neovascularity. In line with our study, previous reports suggest that nimotuzumab is anti-angiogenic and could serve as a targeted therapy against both endothelial cells and tumor cells by disrupting the vascular endothelial microenvironment [ 36 ].…”
Section: Discussionsupporting
confidence: 91%